Economic efficiency of mechanised fishing in Tamil Nadu – A case study in Chennai - Geetha, R.; Narayanakumar, R.; Salim, Shyam S.; Aswathy, N.; Chandrasekar, S.; Srinivasa Raghavan, V.; Divipala, Indira (Indian Journal of Fisheries, 2013)
A study was conducted to analyse the economic efficiency of mechanised fishing in Chennai in Tamil Nadu along the east coast of India. The craft and gear combinations over the years witnessed dramatic changes on account of the huge cost of fishing, duration and depth of operations and maintenance. The mechanised gillnetters showed tremendous increase among the fishing fleet in Chennai mainly due to their assured returns and consistent marketing margin. The present study specifically compares the economic efficiency of mechanised gillnet units and trawlers operating from Chennai. Average operating cost and net income per day for the multiday (MD) gillnetters were ®17,757 and 6,613 whereas in the case of multiday trawlers, the operating cost and net income per day were ®18,095 and ®3,219, respectively. Targeted tuna fishing and better price realisation in the value chain have contributed to better performance of gillnet units. The higher fuel requirement observed for MD trawlers as compared to MD gillnetters is attributed to long distance travelling and the use of mechanical power for propulsion as well as for fishing. The study found that efficiency measures in terms of labour, capital and fuel have established the supremacy of mechanised gillnetters.